A momentary view of engagement in collaborative learning: Triangulation through multimodal data - Haataja, Eetu; Törmänen, Tiina; Somerville, Matthew P.; Malmberg, Jonna; Järvenoja, Hanna; Järvelä, Sanna (Frontline Learning Research, 2025)
Despite recognising momentary challenges while learning, collaborative groups do not necessarily regulate and adapt their learning process according to the demands. Various online measures have recently been explored to unobtrusively study engagement and adaptation in collaborative learning (CL), as it occurs in the classroom. For example, physiological synchrony derived from electrodermal activity (EDA) has been a prominent reflector of momentary engagement in CL. However, how physiological synchrony relates to students’ views about CL, regulation of learning, and performance remains unclear. This study investigates how momentary measures of physiological synchrony, students’ perceived value of CL, and regulation of learning, align and further relate to group performance. The participants were 94 students attending a physics course consisting of four 90-minute lessons and a collaborative exam. Each lesson included a CL task. At the beginning and end of each session, students reported their perceived value of CL. Students’ EDA was recorded to derive physiological synchrony. Co-regulation (CoRL) and socially shared regulation (SSRL) were coded from the video. Results suggest that when groups show higher physiological synchrony, they perceive their CL as less valuable and tend to perform worse in collaborative exams. It seems that self-reports on the value of CL, rather than physiological synchrony, may better reflect the regulation of CL. Interestingly, the association patterns for CoRL and SSRL differed, as frequent CoRL was linked to the less valued CL, while SSRL tended towards a positive relation. The study demonstrates the complex and multidimensional role of momentary engagement in CL.